2005
DOI: 10.1002/chem.200401352
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Dehydrogenation of Methanol with Mononuclear Vanadium‐Oxide Cations

Abstract: The reactions of methanol with mass-selected V+, VOH+, VO+, and VO2(+) cations are studied by Fourier-transform ion-cyclotron resonance (FT-ICR) mass spectrometry in order to investigate the influence of the formal oxidation state of the metal on the reactivity of vanadium-oxide compounds. Interestingly, the most reactive species is the low-valent hydroxide cation VOH+, for which a formal condensation reaction prevails to afford VOCH3(+). In contrast, atomic V+ is oxidized and the high-valent dioxide cation VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 74 publications
2
63
0
3
Order By: Relevance
“…[66] The B3LYP functional has been used previously for a range of vanadium oxide systems, and was shown to give reasonable agreement with available experimental data as well as with higher-level theoretical calculations. [19,20,23,24,27,31,32,[67][68][69][70] Calculations were carried out by using the 6-311 + + G** basis sets for H, C and O, and the SDD effective core potential (ECP) and associated basis sets were used for V. [71] The use of an ECP basis set for V was chosen to allow for direct comparison with the heavier Nb centres. Stationary points were characterized by frequency calculations, and unscaled zero-point energies are included for all species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[66] The B3LYP functional has been used previously for a range of vanadium oxide systems, and was shown to give reasonable agreement with available experimental data as well as with higher-level theoretical calculations. [19,20,23,24,27,31,32,[67][68][69][70] Calculations were carried out by using the 6-311 + + G** basis sets for H, C and O, and the SDD effective core potential (ECP) and associated basis sets were used for V. [71] The use of an ECP basis set for V was chosen to allow for direct comparison with the heavier Nb centres. Stationary points were characterized by frequency calculations, and unscaled zero-point energies are included for all species.…”
Section: Methodsmentioning
confidence: 99%
“…[38,39] The majority of these gas-phase studies have been supported by theoretical calculations. [26,27,31,32,[40][41][42] We recently described the gas-phase catalytic oxidation of methanol to formaldehyde with the mononuclear metavanadate anion [VO 3 ]…”
Section: H T U N G T R E N N U N G (H 2 -Ochr)]mentioning
confidence: 99%
“…Proposals by Johansson et al [30] of participation of solvent molecules such as 2,2,2-trifluorethanol (TFE) in CH activation of alkyl and aryl ligands of Pt II [31,32] were challenged by Chen et al, [33,34] and this led to a discussion about the relevance of gas-phase versus solution chemistry. [35,36] The gas-phase activation of alcohols [37] is described for VO + [38] and Mn + , [39] but no gas-phase alcohol activation by Pt II is found so far. Recently Owen et al showed CH activation of alcohols by Pt II by NMR spectroscopy in solution.…”
Section: IVmentioning
confidence: 99%
“…[87] In [88] Interessant sind auch die theoretischen Arbeiten von Baerends und Mitarbeitern, [89] auch die berechneten Energiebarrieren von einer ¾nderung in der Mikroumgebung der Cluster stark beeinflusst. [89] Eine bemerkenswerte Metallabhängigkeit der konkurrierenden Aktivierung von C-H-und O-H-Bindungen von Methanol wurde auch bei der Elektrospray-Ionisierung von methanolischen Lçsungen von MX 2 (M = Fe, Co, Ni; X = Br, I) beobachtet.…”
Section: Der Erste Schritt: Spaltung Der Starken O-h-oder Der Schwächunclassified